Modern algorithms for statin therapy - V. A. Susekov (Российский кардиологический журнал)
HMG-CoA reductase inhibitors (statins) are a key class of drugs for the treatment and prevention of atherosclerosis and its complications. This class of drugs has become firmly established in Russian and international guidelines with a high level of evidence. However, the use of these drugs in practice is not yet optimal. A significant proportion of patients at very high cardiovascular risk, taking initial doses of statins, do not achieve target levels of low-density lipoprotein cholesterol. The article is devoted to the analysis of international and Russian guidelines for statin monotherapy optimization, including their prescription in primary prevention using cardiovascular risk reclassification, coronary calcium score, carotid Doppler ultrasound and lipoprotein(a) levels.